Robot-Assisted Laparoscopic Adrenalectomy for Rare Myxoid Adrenocortical Carcinoma - Grant Johnson; Kiran Thalody; Umesh Kapur; Thai T. Nguyen (Case Reports in Urology)
Background. Surgical resection remains the standard treatment for adrenocortical carcinoma. Higher rates of local and peritoneal recurrence have been reported with the laparoscopic approach compared to open resection, although the evidence is limited. A dilemma occurs when tumors appear benign in nature, measure >5 cm, or when patients request a minimally invasive surgical approach. We describe the first reported case to date of successful robot-assisted laparoscopic adrenalectomy for myxoid variant adrenocortical carcinoma. Case Presentation. A 38 year old female presented with a large 8.0 cm enhancing left adrenal mass concerning for pheochromocytoma, given refractory hypertension and symptoms of palpitations and headaches. Functional work up was negative. The patient underwent robot-assisted laparoscopic left adrenalectomy after appropriate alpha and beta blockade. Histological sections demonstrated a cortical neoplasm with prominent myxoid changes consistent with myxoid adrenocortical carcinoma. The patient’s symptoms resolved and serial imaging demonstrated no recurrence three and nine months, post-operatively. Conclusion. Myxoid adrenocortical carcinoma is a rare and aggressive entity best managed with surgical resection. Though open resection for invasive adrenal cancer remains the gold standard, minimally invasive approaches are being increasingly used, whether deliberately or not. We describe the first reported robot-assisted laparoscopic adrenalectomy for invasive myxoid adrenocortical carcinoma.